2012
DOI: 10.1158/1078-0432.ccr-11-0679
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA Molecular Profiles Associated with Diagnosis, Clinicopathologic Criteria, and Overall Survival in Patients with Resectable Pancreatic Ductal Adenocarcinoma

Abstract: Purpose: MicroRNAs (miRNA) have potential as diagnostic and prognostic biomarkers and as therapeutic targets in cancer. We sought to establish the relationship between miRNA expression and clinicopathologic parameters, including prognosis, in pancreatic ductal adenocarcinoma (PDAC).Experimental Design: Global miRNA microarray expression profiling of prospectively collected freshfrozen PDAC tissue was done on an initial test cohort of 48 patients, who had undergone pancreaticoduodenectomy between 2003 and 2008 … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
150
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(159 citation statements)
references
References 53 publications
8
150
0
Order By: Relevance
“…For example, miR-21 was increased, whereas miR-146a and let-7 families were decreased [30]. In line with this report, using miRNA microarray, 20 miRNAs were found to be associated with overall survival in PC [31]. Moreover, multiple miRNAs were correlated with lymph node metastasis and high tumor grade.…”
supporting
confidence: 68%
See 1 more Smart Citation
“…For example, miR-21 was increased, whereas miR-146a and let-7 families were decreased [30]. In line with this report, using miRNA microarray, 20 miRNAs were found to be associated with overall survival in PC [31]. Moreover, multiple miRNAs were correlated with lymph node metastasis and high tumor grade.…”
supporting
confidence: 68%
“…Moreover, multiple miRNAs were correlated with lymph node metastasis and high tumor grade. Specifically, up-regulation of miR-21 and down-regulation of miR-34a and miR-30d were associated with poor overall survival [31]. Similarly, a high-throughput miRNAs micorarray unravels the prognostic role of miR-211 in PC [32].…”
mentioning
confidence: 97%
“…Aberrant miR-34a downregulation has been detected in many cancer types, including breast cancer (81), epithelial ovarian cancer (82), prostate carcinoma (80), pancreatic ductal adenocarcinoma (83), hepatocellular carcinoma (84), colon cancer (85), non-small cell lung cancer (86), neuroblastoma (87), glioblastoma (88), malignant peripheral nerve sheath tumors (89), melanoma (80), chronic lymphocytic leukemia (90)(91)(92), and acute myeloid leukemia (93). In many cancer entities, low miR-34a expression is associated with advanced disease and/or poor patient survival, as seen in neuroblastoma (87), epithelial ovarian cancer (82), peripheral nerve sheath tumors (89), breast cancer (81), and pancreatic ductal adenocarcinoma (83). Ectopic miR-34a expression induces cell cycle arrest, apoptosis, and senescence, and inhibits migration and invasion of cancer cells (94).…”
Section: Mir-34amentioning
confidence: 99%
“…The expression of miR-21 has been shown to be involved in the progression of several types of cancers (Kwak et al, 2011;Yang et al, 2011), including PDAC (Bloomston et al, 2007;Szafranska et al, 2007;Nagao et al, 2012), and the up-regulation of miR-21 expression has been shown to correlate with a lower cancer survival rate (Dillhoff et al, 2008;Jamieson et al, 2012). Recent studies also demonstrated that miR-21 modulates the chemosensitivity of cancer cells primarily by targeting PTEN or PDCD4 (Moriyama et al, 2009;Ali et al, 2010;Giovannetti et al, 2010;Tomimaru et al, 2010).…”
Section: Introductionmentioning
confidence: 99%